Surgical therapy and outcome of descending necrotizing mediastinitis in Chinese: a single-center series - Zhao, Zhewei; Ma, Dongjie; Xu, Yuan; Guo, Chao; Li, Shanqing; Wang, Jian; Wang, Mu; Qin, Yingzhi; Liu, Hongsheng (Frontiers in Medicine, 2024)
Descending Necrotizing Mediastinitis (DNM) is an acute and often fatal infection that affects the neck and mediastinum. DNM treatment consists of broad-spectrum antibiotics, early diagnosis, and surgical debridement with multidisciplinary cooperation. However, owing to the rarity and complexity of this disease, the mortality rate is high. This retrospective study analyzed a single-center experience of managing DNM in Chinese patients over the last ten years.A single-center, retrospective, observational, and descriptive study was conducted on 31 patients with DNM at Peking Union Medical College Hospital from 2012 to 2022. Case report forms were used to collect data which were then analyzed with a focus on surgical management and outcomes.This study examined the outcomes of 31 patients diagnosed with DNM at our hospital. The most common comorbidities on admission were hypertension (48%) and diabetes mellitus (42%). The degree of diffusion of DNM according to Endo's classification was classified as follows: type I in 7 patients (22.6%), type IIA in 5 (16.1%), and type IIB in 19 patients (61.3%). Among these patients, 13 (41.9%) were found to have a single microbial infection, while 16 (51.6%) were found to have polymicrobial infections. In all cases, neck drainage was performed via cervicotomy, with multiple drains (64.5%) and vacuum sealing drainage (VSD) (35.5%). Mediastinal drainage was performed via a cervical mediastinotomy (51.6%), video-assisted thoracic surgery (VATS) (41.9%), or thoracotomy (6.5%). The 30-day mortality rate was 25.8% and 24.0 days of the average length of hospital stay.Early accurate diagnosis and timely intervention have been shown to be correlated with a positive prognosis. Cervicothoracic CT (computed tomography) is essential for the diagnosis, staging, and evaluation of the optimal surgical treatment. Cervicotomy and video-assisted thoracoscopic surgery with percutaneous drainage is effective, even in advanced cases.Additionally, the application of VSD in cervical incision did not improve prognosis but may shorten the length of ICU (intensive care unit) and hospital stays.